Detection of Antibodies against Japanese Encephalitis Virus in Raccoons, Raccoon Dogs and Wild Boars in Japan - OHNO, Yoshito; SATO, Hiroshi; SUZUKI, Kazuo; YOKOYAMA, Mayumi; UNI, Shigehiko; SHIBASAKI, Takahiro; SASHIKA, Mariko; INOKUMA, Hisashi; KAI, Kazushige; MAEDA, Ken (Journal of Veterinary Medical Science, 2009)
Japanese encephalitis virus (JEV) infects numerous animal species including humans, horses and pigs. In this study, antibodies against JEV in feral raccoons (Procyon lotor), wild boars (Sus scrofa) and raccoon dogs (Nyctereutes procyonoides) in Japan were examined. The results showed that 40.7% (22 out of 54), 64.5% (40 out of 62), 69.1% (47 out of 68) and 0% (0 out of 20) of raccoons in Hyogo, Osaka, Wakayama and Hokkaido, respectively, had virus-neutralizing antibodies against JEV. In addition, 83.3% (30 out of 36) of wild boars and 63.2% (12 out of 19) of raccoon dogs in Wakayama were seropositive for JEV. There were no significant differences in seroprevalence of JEV between males and females or between adults and juveniles in these wild animals. JEV seroprevalence was compared between 37 raccoons and 30 wild boars captured in a limited period (November 2007 to February 2008), and we found that wild boars (86.7%) were significantly more seropositive for JEV antibody than raccoons (59.5%). In conclusion, JEV was prevalent in wild mammals, indicating that the possibility of JEV infection in humans may still be high in Japan. In addition, these wild animals may be good sentinels to estimate JEV infection risk in residents, as they live near humans and are not vaccinated.